The dislocation of Nigerian identities as the result of hegemony in Adichie’s Purple Hibiscus - Rinanti Arnisa; Imas Istiani; Zuhrul Anam (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
The concept of individuality's sense of self may trigger some conflicts in an ex-colonized country. The British colonized Nigeria for sixty years, and the colonization formally ended after Nigeria declared its independence on the first of October, 1960. A new Nigerian dictatorial government performs hegemony as the remnant of colonization. This phenomenon is represented in Purple Hibiscus, which is based on the military dictatorship in Nigeria between 1980 and 1999. This study aims to find the forms of hegemony and its negative impacts on the dislocation of identity. The research method is qualitative. The data is analyzed by Gramsci's hegemony and is supported by the concept of diaspora in postcolonialism. The data is obtained based on the dominant and subordinate conflicts. Purple Hibiscus presents three forms of hegemony: restricted media, religion, and the English language. The novel shows the negative impacts of hegemony: isolation, no individual choices, oppression, and dislocation of identity. The process of identity dislocation is portrayed through emotional attachment and the realization of life-changing seen through the acceptance and interaction with American people with different backgrounds, diverse cultures, and distinct environments.